2024
DOI: 10.1029/2023ja032260
|View full text |Cite
|
Sign up to set email alerts
|

The Altitudinal Dependences of the Inter‐Hemispheric Asymmetry in the Mid‐Latitude Ionospheric Post‐Midnight Enhancement During Equinox

H. Zhang,
H. T. Cai,
X. Wan
et al.

Abstract: Using observations from multi‐satellites at different altitudes, including the CHAllenging Minisatellite Payload (CHAMP), the Gravity Recovery and Climate Experiment, Swarm B, and Defense Meteorological Satellites Program F17, the ionospheric post‐midnight enhancement at mid‐latitudes and the associated inter‐hemispheric asymmetry during equinox are investigated in this study. During equinox months, the ionospheric electron density enhancement during post‐nighttime at mid‐latitudes is visible in both hemispher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…The present DMSP observations showed that the H + was the dominant ion at ∼4 LT at 840 km altitude and its latitude profiles presented two peaks around 40°N/S during the quite times on 20-24 August 2018. The previous studies showed that the nighttime ionosphere was not always decreased monotonously after the cease of the sunlit, and it sometimes presented enhancement in middle latitudes (e.g., Xiong & Lühr, 2014;Chen et al, 2015;Zhang et al, 2024;Zhong et al, 2019). Several mechanisms are suggested to induce the nighttime enhancement of the ionosphere F2 region, including the equatorward neutral wind and the downward flux from the plasmasphere and topside ionosphere (e.g., Chen et al, 2011;Jee et al, 2005;Kotov et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The present DMSP observations showed that the H + was the dominant ion at ∼4 LT at 840 km altitude and its latitude profiles presented two peaks around 40°N/S during the quite times on 20-24 August 2018. The previous studies showed that the nighttime ionosphere was not always decreased monotonously after the cease of the sunlit, and it sometimes presented enhancement in middle latitudes (e.g., Xiong & Lühr, 2014;Chen et al, 2015;Zhang et al, 2024;Zhong et al, 2019). Several mechanisms are suggested to induce the nighttime enhancement of the ionosphere F2 region, including the equatorward neutral wind and the downward flux from the plasmasphere and topside ionosphere (e.g., Chen et al, 2011;Jee et al, 2005;Kotov et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The latter indication is due to the constitutional difference between the two structures. The midlatitude extra peaks could be observed down to the CHAMP altitude below 400 km (Zhang et al, 2024), indicating that the ionospheric O + plays a dominant role. In addition, we examined several DMSP extra peak cases and found O + dominance (not shown).…”
Section: Possible Formation Mechanismmentioning
confidence: 96%